Design and Implementation of a LAN-Based Personal Home Media Streaming Server - Mega Christin Morys Lase; Finis Hermanto Laia; Progresif Buulolo; Karuniaman Buulolo; Kristine Wau (STMIK Methodist Binjai, 2026)
Advancements in computer network technology have created a need for efficient multimedia content-sharing systems that do not rely on an internet connection, and one viable solution is to build a personal home streaming media server based on a Local Area Network (LAN), prompting this research to design and implement a media streaming system utilizing Digital Living Network Alliance (DLNA) features within the Windows operating system to enable direct access to multimedia files from other devices on the local network; the study employs a design and implementation methodology encompassing requirements analysis, system design, network configuration, media streaming service configuration, and system testing, which involved IP address configuration, connectivity verification via the ping command, and streaming service validation using Windows Media Player on client computers, with the results demonstrating successful connectivity between the server and client computers within the LAN, proper activation of the DLNA service, and successful access and streaming playback of multimedia files without the need for downloading or experiencing buffering, thus proving that the developed system provides a simple, efficient, and easily implementable multimedia sharing solution suitable for home environments or small-scale local networks.